Oryctes Rhinoceros bottle opener - Ariff, Ahmad Fairuz; Raja Ahmad Effendi, Raja Ahmad Azmeer; Baharuddin, Nasir (Universiti Putra Malaysia Press, 2013)
The bottle opener is a product that functions as a removal of metal bottle caps that usually display simplicity in its design, particularly in the early days it was introduced. At present, most of the design for this product seems to display modern appearance but less consideration in the user comfort. Therefore, a new design of the bottle opener is produced which took consideration not only on the appearance but also the ergonomic aspect that uses plastic together with semi-curve lines providing users a steady thumb and firm hand grip. It is inspired by nature (insect) in which it mimicked the Rhinoceros beetle's body parts.